2021
DOI: 10.1021/acs.jpcc.1c08296
|View full text |Cite
|
Sign up to set email alerts
|

Structural Chemistry, Flexibility, and CO2 Adsorption Performance of Alkali Metal Forms of Merlinoite with a Framework Si/Al Ratio of 4.2

Abstract: Small pore zeolites that show framework flexibility, such as merlinoite (topology type MER), possess a high potential for the selective adsorption of small gas molecules including CO 2 . The CO 2 adsorption properties of Na-, K-, and Cs-exchanged forms of a merlinoite zeolite with Si/Al = 4.2 have been measured at 298 K, and in situ PXRD was used to follow their structural response to dehydration and CO 2 uptake. The Na-and Cs-forms convert from a wide-pore to a narrow-pore form upon dehydration, while the K-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Similar but more severe trapdoor effects upon CO 2 adsorption are observed in low silica aluminosilicate CHA materials containing potassium and prepared in the absence of an OSDA. ,, Nonetheless, said CHA materials operate poorly under the presence of water, which is a major issue for industrial implementation . Merlinoite is another zeolite which presents guest-induced flexibility upon CO 2 adsorption and very promising CO 2 /CH 4 selectivities. ,, Additionally, Hong et al have reported its OSDA-free synthesis, making it a very promising and potentially cheap CO 2 adsorbent …”
Section: Chemical Separations By Zeolitesmentioning
confidence: 91%
See 3 more Smart Citations
“…Similar but more severe trapdoor effects upon CO 2 adsorption are observed in low silica aluminosilicate CHA materials containing potassium and prepared in the absence of an OSDA. ,, Nonetheless, said CHA materials operate poorly under the presence of water, which is a major issue for industrial implementation . Merlinoite is another zeolite which presents guest-induced flexibility upon CO 2 adsorption and very promising CO 2 /CH 4 selectivities. ,, Additionally, Hong et al have reported its OSDA-free synthesis, making it a very promising and potentially cheap CO 2 adsorbent …”
Section: Chemical Separations By Zeolitesmentioning
confidence: 91%
“…515 g Breakthrough data of 10/30/50 (CO 2 /CH 4 /He), 1 bar total prressure. 517 h Breakthrough data of a CO 2 /CH 4 40:60 mixture 520 at 5 bar total pressure. i Breakthrough data of equimolar CO 2 /CH mixtures 262 the search for better adsorbents that can further improve the efficiency and economy of the process is still a very active research field.…”
Section: Separation Of Carbon Dioxidementioning
confidence: 99%
See 2 more Smart Citations
“…3 Cation gating appeared in different cationic form zeolites as cationic displacements in the presence of CO 2 or its mixtures. 3–6 The flexibility-driven effects are observed in the same systems in parallel. More precisely, the unusual growth of CH 4 adsorption of Me′MER zeolites (Me′ = Na, K, Cs with different Si/Al modulus) after the minor addition of CO 2 to the gas has been interpreted as a consequence of the transformation of the 8R windows.…”
Section: Introductionmentioning
confidence: 99%